Coalizões de interesses e a configuração política da agricultura familiar no Brasil - Santos, Fábio Pereira dos (2011)
This research intends to explain the emergence and development of family farming public policy in Brazil since the early 1990’s. In this period two advocacy coalitions emerged – in defense of family farming and in defense of corporate agriculture – with opposing beliefs on the model of agriculture the country should adopt. Throughout this process the fundamental actors in each coalition rebuilt their own political identities: traditional rural landowners’ framework from the 1980’s is modernized as agribusiness; rural workers are now also family farmers. The development of family farming public policies is treated as a path dependent process. The period in which Pronaf (National Program for Strengthening of Family Farming) was created is characterized as a critical juncture signaling the beginning of a new path of public policy in Brazil. The existence of two advocacy coalitions was one of the most relevant forces at that juncture, but only the convergence of several factors, among them social pressure from family farmers, the challenging of the traditional ideas about the rural world up to then dominant in Brazilian thought and socioeconomic and political factors made possible the creation of these new policies. Once adopted, family farming policies have their institutional development constrained by the initial choices, and create a new environment for actors intervention. Family farming policies began to produce effects on players in a process of policy feedback that was crucial to the expansion and institutional consolidation of these policies. The first effect was to intensify the dispute between the two advocacy coalitions over the public policies for the rural areas. The second policy effect was the strengthening of family farmers’ organizations. Policies have also contributed to increasing the participation of family farmers in the formal political system; they have produced political impacts on beneficiaries and on politicians and voters, forging legitimacy for that social category. Finally, family agriculture policies have produced changes in state capacity and organization, with the creation of a new Ministry (MDA) and increasing the volume and scope of policies for family farming, including other areas of federal government as well as in municipal and state level governments.